2008
DOI: 10.3171/jns/2008/109/10/0723
|View full text |Cite
|
Sign up to set email alerts
|

Mesencephalic ependymal cysts: treatment under pure endoscopic or endoscope–assisted keyhole conditions

Abstract: A symptomatic mesencephalic ependymal cyst is an indication for neurosurgical intervention. These cysts can be treated successfully and most likely definitively by a pure endoscopic or endoscope-assisted keyhole neurosurgical technique. There were no morbid conditions or death due to the procedures in this group of 8 patients. Therefore, the authors regard these surgical procedures to be good alternatives to treatments such as shunt placement or stereotactic aspiration of the cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…They also concluded that ventriculo-cystostomy or cyst-cisternostomy is needed to effectively treat cysts causing brainstem compression. Since these cysts are located deep within the parenchyma and neural tissue has to be crossed to reach the cyst cavity, preference should be given to minimally invasive treatment [17]. In this perspective, endoscopy can, in our opinion, play a primary role.…”
Section: Casementioning
confidence: 97%
See 1 more Smart Citation
“…They also concluded that ventriculo-cystostomy or cyst-cisternostomy is needed to effectively treat cysts causing brainstem compression. Since these cysts are located deep within the parenchyma and neural tissue has to be crossed to reach the cyst cavity, preference should be given to minimally invasive treatment [17]. In this perspective, endoscopy can, in our opinion, play a primary role.…”
Section: Casementioning
confidence: 97%
“…MRI spectroscopy parameters also reflect the paucity of tissue alterations [10]. Lastly, they must be differentiated from mesencephalic ependymal cysts, as described by Conrad [17].While frequent elsewhere in the brain, expanding dilations of Virchow-Robin spaces are very rarely located in the midbrain [1]. They cause two main categories of symptoms: those caused by midbrain compression (e.g., Benedikt's syndrome [18,19] or Parkinson-like syndrome) and those by secondary obstructive hydrocephalus, with intracranial hypertension or signs of normal pressure hydrocephalus.…”
Section: Casementioning
confidence: 99%
“…Conrad et al [1 ]presented 8 patients with mesencephalic cysts, mostly ependymal, treated successfully with an endoscopy-assisted or purely endoscopic keyhole approach. They demonstrated that mesencephalic cystic lesions can be fenestrated via an approach through the cisterna ambiens.…”
Section: Discussionmentioning
confidence: 99%
“…For midbrain lesions, especially intraparenchymal (as opposed to exophytic), when a decision is made to treat surgically, eloquent neural tissue must be traversed before the lesion is reached. Consequently, careful planning of the trajectory is mandatory in order to avoid surgical damage [1]. …”
Section: Discussionmentioning
confidence: 99%
“…8 Differential diagnoses on MRI include arachnoid and intraventricular echinococcal cysts, whereas colloid, epidermoid and dermoid cysts typically show high signal intensity on T1-weighted and low signal intensity on T2-weighted MRI. 9,[11][12][13] Retrospective analyses of endoscopic fenestration of cysts arising from various locations revealed a lower recurrence rate than shunt placement or surgical aspiration; 11 however, reaccumulation of cyst contents requiring reoperation after all methods of fenestration or drainage has been described. The fluid within the cyst is similar to cerebrospinal fluid (CSF) although it may contain variable amounts of protein and lipids.…”
Section: Introductionmentioning
confidence: 99%